2022
DOI: 10.1177/20406223221080646
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of using calligraphic activity to treat people with schizophrenia: a randomized controlled trial in Southern Taiwan

Abstract: Background: Prior research has shown preliminary evidence that calligraphy activity improves various body functions and decreases severity of psychotic symptoms in individuals with schizophrenia. However, major limitations of earlier studies include small and heterogeneous samples. The current large-scale randomized controlled trial examined effects of calligraphy activity on cognition (including attention), emotions, psychotic symptoms, quality of life, and mood in people with schizophrenia. Methods: One-hund… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…Thus, scientists are looking for the methods of nonpsychotropic drugs to effectively improve these side effects, namely, calligraphy activity (W. Y. Huang et al, 2022), psychotherapy interventions (Roberts et al, 2021), aerobic exercise (Firth et al, 2017), and so forth. Early clinical research reported that the presence of moderate to severe depressive symptoms can occur at any point during SCZ (J.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, scientists are looking for the methods of nonpsychotropic drugs to effectively improve these side effects, namely, calligraphy activity (W. Y. Huang et al, 2022), psychotherapy interventions (Roberts et al, 2021), aerobic exercise (Firth et al, 2017), and so forth. Early clinical research reported that the presence of moderate to severe depressive symptoms can occur at any point during SCZ (J.…”
Section: Introductionmentioning
confidence: 99%
“…However, in view of the lack of efficacy improvement regarding negative symptoms, metabolic syndrome, and cognitive function, the SGAs were limited in clinical application (Divac et al., 2014 ). Thus, scientists are looking for the methods of nonpsychotropic drugs to effectively improve these side effects, namely, calligraphy activity (W. Y. Huang et al., 2022 ), psychotherapy interventions (Roberts et al., 2021 ), aerobic exercise (Firth et al., 2017 ), and so forth. Early clinical research reported that the presence of moderate to severe depressive symptoms can occur at any point during SCZ (J. Huang et al., 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…The studies were published between 2005 and 2023, with sample sizes ranging from 22 to 140. Two studies were conducted in the United Kingdom [ 35 , 36 ], two in Taiwan [ 37 , 38 ], one each in Germany [ 39 ] and Turkey [ 40 ], and the remaining twenty-five in China [ 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 ]. A total of 3037 individuals with schizophrenia participated in these studies.…”
Section: Resultsmentioning
confidence: 99%
“…The JPC is the largest psychiatric center in Taiwan, and it provides mental health services and psychiatric treatment to people residing in southern Taiwan. Therefore, the JPC could refer to the current study a sufficient number of participants with psychiatric diagnoses of SUDs, ADHD, and SZ [ 30 , 33 , 34 ].…”
Section: Methodsmentioning
confidence: 99%